A Very Long Foreign Body in the Bladder - Atsushi Imai; Yuichiro Suzuki; Yasuhiro Hashimoto; Atsushi Sasaki; Hisao Saitoh; Chikara Ohyama (Advances in Urology)
In the urinary tract, foreign body is most commonly found in the urinary bladder. But it is anatomically very difficult for a man to self-insert a long object into the urinary bladder. Here we report a case of a 49-year-old Japanese man who has inserted a 140-cm vinyl tube in the bladder for masturbation. He could not retrieve it, and the bladder foreign body remained in this position for about two years. He was referred to our hospital and open surgery was performed.